A Content Analysis of Activities in English Textbook “When English Rings A Bell” - Mutia Amalia Putri (Research in English and Education Journal, 2018)
This study aimed at identifying and analyzing the levels of activities available in English textbook “When English Rings a Bell” for eighth grade by using cognitive domain of Bloom’s Taxonomy. Content analysis was applied in 12 chapters of textbook in order to know to what extent the activities emphasized on Lower Order Thinking Skills (LOTS) and Higher Order Thinking Skills (HOTS). The activities were collected, listed, and analyzed based on cognitive domain levels of revised Bloom’s Taxonomy; remembering, understanding, applying, analyzing, evaluating, and creating. The results showed that the most dominant cognitive domain level focused on remembering level which provided 93 activities (54.4%), followed by applying level (19.3%), analyzing level (11.1%), evaluating level (8.2%), understanding level (4.1%), and creating level (2.9%). It was concluded that this textbook emphasized on LOTS (133 activities/77.8%).